When the wall is broken: Rural-to-Urban migration, perceived inequality, and subjective social status in China. (December 2022) - Wei, Lai
Abstract: Economic development in China in the recent decades features both striking between-region economic inequality and robust between-region migration flow. What happens when the largest internal migration in human history cooccurs with severe regional inequality? This article investigates how migration affects subjective outcomes with a particular focus on the influence of inequality and social comparison. Using a nationally representative longitudinal survey dataset that tracks migrants through the migration cycle, I found that migration has a negative causal effect on subjective social status, and a positive causal effect on perceived inequality. The effects on subjective social status and perceived inequality persist even after migrant workers return home. Employing a novel operationalization of reference group, I show that migration's persisting negative effect on subjective social status is a result of its lasting effect on reference standard. In sum, migrants' reference standards are changed by the migration experience, and the switch has lasting effects on subjective social status. I discuss the implications of the findings on the theories of subjective inequality, subjective social status, and reference group.